2015
DOI: 10.1108/jeim-04-2014-0046
|View full text |Cite
|
Sign up to set email alerts
|

Examining mobile based payment services adoption issues

Abstract: Purpose – The purpose of this paper is to make a unified approach in identifying the issues affecting usage intention of mobile-based payment services. The work aims to analyze the reduced factors from data obtained from a survey to highlight the influencers of usage intention mobile-based payment in an integrated manner by incorporating the technical characteristics, technology-specific characteristics, user-specific characteristics and task-specific characteristics. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
13
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(16 citation statements)
references
References 47 publications
(49 reference statements)
2
13
1
Order By: Relevance
“…The perception of a lack of control over technology diminishes the ability to deal with uncertainties that new technology can generate [49,57]. The difficulty of adopting new technology such as OFDO service apps could cause discomfort for individuals (i.e., consumers), and this would influence their usage of the app [68]. OFDO service apps are still considered a new experience in developing countries, causing a high level of discomfort, and they will not get more adoption until consumers feel comfort using these apps [69].…”
Section: Discomfortmentioning
confidence: 99%
“…The perception of a lack of control over technology diminishes the ability to deal with uncertainties that new technology can generate [49,57]. The difficulty of adopting new technology such as OFDO service apps could cause discomfort for individuals (i.e., consumers), and this would influence their usage of the app [68]. OFDO service apps are still considered a new experience in developing countries, causing a high level of discomfort, and they will not get more adoption until consumers feel comfort using these apps [69].…”
Section: Discomfortmentioning
confidence: 99%
“…Subsequent to his work, practicing scholars explored the field using established theoretical frameworks and some scholars even extended the established frameworks by developing and validating new constructs which they felt were largely missing in prior literature (Madan & Yadav, 2016). Furthermore, some scholars extended the methodological perspective by incorporating advance level of statistical analysis in their research work (Gbongli et al, 2019;Leong et al, 2013;Liébana & Lara, 2017;Upadhyay & Chattopadhyay, 2015;Yang & Sattayatham, 2016). The next highly cited article in the league have been contributed by Kim et al (2010).…”
Section: Most Influential Workmentioning
confidence: 99%
“…Several m-payment studies have discussed antecedents from the perspectives of external and social influences (Teo et al, 2015;Kapoor et al, 2015;Phonthanukitithaworn et al, 2015;Qasim and Abu-shanab, 2016;Liébana-Cabanillas et al, 2015;Phonthanukitithaworn et al, 2016;Qasim and Abu-shanab, 2016). Some researchers have focused on service performance perspectives, such as usefulness (Sanayei et al, 2011;Padashetty and Kishore, 2013;Liébana-Cabanillas et al, 2014;Upadhyay and Chattopadhyay, 2015;Upadhyay and Jahanyan, 2016;Molina-Castillo et al, 2016), ease of use (Sanayei et al, 2011;Liu et al, 2011;Padashetty and Kishore, 2013;Liébana-Cabanillas et al, 2014;Arvidsson, 2014;Upadhyay and Chattopadhyay, 2015;Upadhyay and Jahanyan, 2016;Molina-Castillo et al, 2016), convenience (Hayashi, 2012;Shin et al, 2014;Kaitawarn, 2015;Teo et al, 2015) and system quality (Upadhyay and Chattopadhyay, 2015;Upadhyay and Jahanyan, 2016). Studies pertaining to the role of relationship quality have concluded that satisfaction (Sanayei et al, 2011;Dlodlo, 2015) and trust (Padashetty and Kishore, 2013;Liébana-Cabanillas et al, 2014;Arvidsson, 2014;Zhou, 2014;Dlodlo, 2015;Phonthanukitithaworn et al, 2015;Phonthanukitithaworn et al, 2016;Qas...…”
Section: Literature Review and Hypothesis Developmentmentioning
confidence: 99%
“…M-payment is a process of transferring money through mobile technology and requires due authorization and conformance to a legal policy (Upadhyay and Chattopadhyay, 2015;Apanasevic et al, 2016). Some researchers have suggested that m-payments can replace debit and credit cards (Eun et al, 2013;Oliveiraa et al, 2016), whereas other research indicated that m-payment does not replace physical cards but is likely to serve as a substitute for cash payment in the adoption stage (Trütsch, 2016).…”
Section: Introductionmentioning
confidence: 99%